Spatial and temporal trend analysis of discharge and water quality, Case study: Chamriz-Pol Khan reach of Kor river - Vida Pasandi Pour; Homa Razmkhah; Alireza Fararouie; Amin Rostami Ravari (مهندسی منابع آب)
Introduction: Temporal analysis of discharge gives information for water resources management. Meteorological variables change like precipitation has important effects on water resources. Management of pollutions has significant influences on water quality of the region. Methods: Temporal trend of discharge and water quality of Kor river, for a 46 year, in Chamriz and Pol Khan stations, analysed, using Man Kendall and Sen slope trend analysis. Statistical distributions fitted to the data, then the parameters forecasted for different return periods, and compared in the stations. Water quality parameters compared with standard values of different uses. Findings: Results showed that Pol Khan monthly average discharge is greater than Chamriz, which could be resulted from the entry of other rivers such Sivand. For 2-, 5- and 10-year return periods, the forecasted discharge of Pol Khan is greater than Chamriz, but for 20 and 50 years Chamriz discharge is more, which could result from River water control in Doroudzan Dam. In Chamriz all of the parameter’s average are in standard limits. In Pol Khan the TDS and EC values are higher than domestic use standards, but other parameters are in the limits. Except for EC, other parameters are in the limits of livestock and poultry, and irrigation standards. All of the parameter in Pol Khan are higher than Chamriz except PH. Trend analysis showed decreasing of discharge in the both stations. In Chamriz Na and SAR showed no trend, SO4 and PH had a decreasing and others had increasing. In Pol Khan, PH showed decreasing, and the others increasing. Except PH, all of the forecasted values, for all return periods, in Pol Khan are higher than Chamriz. Reduction of agricultural pollution, prevention of wastewater entry and treatments could be effective for improvement of water quality